2015
DOI: 10.1016/j.jstrokecerebrovasdis.2014.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Prestroke Living Situation and Depression Contribute to Initial Stroke Severity and Stroke Recovery

Abstract: Substantial evidence from both experimental and clinical studies has demonstrated that social isolation can increase stroke incidence and impair recovery. Social isolation leads to higher rates of recurrent stroke but is often not reported as a risk factor. We examined prospectively collected stroke center database variables, which included pre-stroke living situation, to determine if social isolation could be determined from existing data using living arrangement as a proxy. Patients were categorized into 4 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…One study showed that receiving help at home prior to stroke predicted poor outcome after stroke (12). Another showed that patients living alone or with a spouse had better outcomes than patients with visiting services or living with family; the latter two groups were found to have poorer pre-stroke function (33). While our results were non-linear and should be explored in future studies; they could be explained if higher levels of pre-stroke social support reflect poorer pre-stroke function.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that receiving help at home prior to stroke predicted poor outcome after stroke (12). Another showed that patients living alone or with a spouse had better outcomes than patients with visiting services or living with family; the latter two groups were found to have poorer pre-stroke function (33). While our results were non-linear and should be explored in future studies; they could be explained if higher levels of pre-stroke social support reflect poorer pre-stroke function.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was found that stroke patients with a severe prestroke disability have a virtually 50% risk of deceasing. It seems that women are particularly liable of depression after stroke and that this is related to a greater stroke severity ( 159 ). Of note are patients with migraine that to a large proportion suffer from small vessel disease ( 160 ) or hemorraghic stroke ( 161 ).…”
Section: Disease-related Limitations Of the Recovery Potentialmentioning
confidence: 99%
“…Despite all of the above, we have a relatively limited understanding of why depression may follow a heart attack or stroke. Although social support may have clinical management and prognostic implications for those experiencing a heart attack or stroke, social support measures such as social isolation are absent from many large stroke databases (Aron et al , ). While there is more information linking poor social support to depression post‐heart attack, these studies often are relatively small, are geographically limited, and/or do not prospectively evaluate social support prior to the heart attack (Frasure‐Smith et al , ; Dickens et al , ).…”
Section: Introductionmentioning
confidence: 99%